062 Sex Differences in Slow Wave Sleep Following Evening Binge Alcohol Consumption. (3rd May 2021) - Greenlund, Ian; Bigalke, Jeremy; Tikkanen, Anne; Nicevski, Jennifer; Smoot, Carl; Carter, Jason
Abstract: Introduction: Binge alcohol consumption alters normal sleep architecture, often via increased slow wave sleep (SWS) and decreased rapid eye movement (REM) sleep. Women may be more susceptible to the sedative effects of alcohol during blood alcohol content (BAC) decrease as they report higher subjective sleepiness scores prior to bedtime. The purpose of the present study was to examine changes in SWS between men and women following binge alcohol consumption and determine the relation between BAC change at lights out and subsequent sleep architecture. Methods: Twenty-three participants (11 men, 12 women) between the ages of 21–45 years were tested twice, once after evening binge alcohol consumption and once after fluid control (randomized, cross-over design). The alcohol dose was based on body weight and sex (1g/kg in men, 0.85g/kg in women) and served as a 4–5 drink equivalent consumed over two hours. Breath alcohol content (BrAC) was monitored in 15-minute increments from first drink consumption to lights out. Overnight polysomnography (PSG) was recorded in each individual and scored by a board-certified sleep physician. Statistical analysis consisted of repeated measures ANOVA and Pearson correlation (p>0.05). Results: Age (24±4 vs. 26±6 years) and BMI (27±4 vs. 27±4 kg/m2) were similar between men and women. Peak BrAC (0.10±0.02% vs. 0.10±0.02%) and percent change (-19±11% vs. -19±11%) in BrAC from peak to lights out were also similar between the sexes. Peak BrAC was significantly correlated to the percentage of SWS in women (r=-0.71; p=0.01), but not men (r=-0.25; p=0.45). Similarly, the percent change in BrAC from peak to lights out was significantly correlated to the percentage of SWS in women (r=-0.66; p=0.02), but not men (r=-0.40; p=0.22). The SWS and REM latencies were not associated with either peak or lights out BrAC in both men and women. Conclusion: Peak BrAC, and the rate of BrAC clearance prior to lights out, appear to impact SWS differently in men and women. Specifically, women appear to have more SWS in response to high BrAC than their male counterparts, suggesting a stronger depressor impact with regards to SWS in women. Support (if any): National Institutes of Health (AA-024892; U54GM115371; P20GM103474).